Nursing Student's Experiences of Meditation on Twin Hearts During Eight Weeks Practice: A Qualitative Content Analysis - B.M. Meena MA, MBA; B. Manasa MSc; Vinu Vijayakumar MSc; Kiran Kumar K. Salagame PhD; Srikanth N. Jois PD (SAGE Publishing, 2021)
Background Meditation on Twin Hearts (MTH) involves blessing the earth to alleviate the sufferings, and praying for the well-being of the entire society using heart and crown chakra. This meditation is characterized by mechanisms of loving-kindness, self-healing imagery, and open awareness. Purpose This study aims to identify the experiences and perceived benefits associated with practicing MTH by nursing students. Method Qualitative method using content analysis was used to study meditation experiences. After obtaining the informed consent, 22 nursing students were introduced to MTH. Experiences and feedback from meditation sessions were reported each day during their 8 week practice. Nursing students also answered seven open-ended questions on the last day of the meditation session. Findings The verbatim descriptions of experiences reported by nursing students were abstracted to elements (17), properties (6), and categories (2). Identified properties are positive experiences, experiences of awareness, energy experiences, tangible outcomes, physiological reactions, and feedback on the study program. Conclusion The experiences narrated by nursing students include positive affective experiences, health benefits, resolution of problem, awareness and energy experiences, and prosocial tendencies. These findings indicate that MTH would enhance the well-being of the nursing students and could be used as a self-care measure.